Contribuição ao estudo de pilares pré-moldados de concreto em etapa transitória - Otrente, João Francisco (2022)
During its production, the precast structures go through different stages called the transitory stage and, consequently, through different static schemes and requests. The precast columns during this stage have a static beam scheme which can cause particular design situations in which the transitory stage is critical for the design. In addition, many designers do not consider the loss of stiffness due to eventual cracking of the element at this stage. The objective of this work is to evaluate how the application of prestressing with pre-tension helps in the performance of precast concrete columns in particular design situations in which the formation of cracks in the phases of the transitory stage can occur. To achieve this, a case study was carried out on a precast concrete column with a critical transitory stage. The column was analyzed in reinforcement concrete with different static schemes and later in prestressed concrete containing two arrangements of active reinforcement. The analysis of the element in question was performed using the following parameters: tension in the reinforcement, cracking moment, amount of reinforcement and secant flexion stiffness via analytical methods. In addition, a parametric analysis was carried out during the demolding phase and lifting in assembly, whose parameters obtained from the variation of the position of the lifting loops were: bending moments, tension in the reinforcement and stiffness reduction coefficient for the most requested sections. Based on the analysis of the results, it is concluded that when using three lifting loops, the column presented a stiffness of up to 0.84.EI during demolding. With the introduction of prestressing, the column with two lifting loops resulted in a stiffness of up to 0.90.EI at the end of transitory stage. Still, it was observed, via parametric analysis, that the column only presented a stiffness bigger than 0.50.EI when the stress level in the passive reinforcement was less than 0.30.fyk. Finally, it is understood that the loss of stiffness during the transitory stage must be accounted for.